2017
DOI: 10.12913/22998624/68468
|View full text |Cite
|
Sign up to set email alerts
|

Buckling Behaviour of Single-Walled Carbon Nanotubes Under Axial Loading

Abstract: We investigate the behaviour of a single-walled Carbon Nanotube under axial compressive line load applied at both edges. The expected buckling response is studied by application of a molecular computation model. We formulate a global potential and search for its minimum to obtain the equilibrium configuration. The critical nanotube diameter, when local shell buckling occurs, is measured with two parameters: the value of compression loading and tube diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Hence, transforming plastic wastes into new materials of great value like carbon nanotubes (CNTs) is a promising route for environmental sustainability [6,7]. CNTs have become much-researched material recently [8], owing to their distinctive and captivating characteristics [9], such as high tensile strength, mechanical strength, electrical toughness, high surface-to-volume ratios for use in different fields like electronics, sensors, biomedical, energy storage, reinforced composites, water treatment and many more [3,[10][11][12][13]. The use of CNTs is still limited due to their high cost [14], hence, the use of recycled plastics as cheap feedstocks to produce CNTs would provide a sustainable way of PWs management [15].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, transforming plastic wastes into new materials of great value like carbon nanotubes (CNTs) is a promising route for environmental sustainability [6,7]. CNTs have become much-researched material recently [8], owing to their distinctive and captivating characteristics [9], such as high tensile strength, mechanical strength, electrical toughness, high surface-to-volume ratios for use in different fields like electronics, sensors, biomedical, energy storage, reinforced composites, water treatment and many more [3,[10][11][12][13]. The use of CNTs is still limited due to their high cost [14], hence, the use of recycled plastics as cheap feedstocks to produce CNTs would provide a sustainable way of PWs management [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the use of the crystal-based finite element analysis method (FEM) for modeling of exclusively mechanical properties of small and very large single-body and multi-body (>1.0 × 105 atoms) structural models is becoming popular as the FEM approach offers significantly reduced computational time and lowers the demand for resources while rendering highly plausible simulation results. Crystal-based FEM is a versatile continuum mechanics approach used for predicting mechanical properties and deformation-induced crystallographic structures, and it can be applied to solving both elastic-plastic and purely elastic problems of multi-body systems [Ma et al, 2008] and complex CNT model structures [Wang et al, 2009[Wang et al, , 2016Faria et al, 2016;Litak, 2017;Robinson and Adali, 2017;Bocko and Lengvarský, 2017;Timesli et al, 2017;Hosseini-Hashemi and Ilkhani, 2017;Nishimura et al, 2017]. Investigation concerning the mechanical response and structural stability of these quasi-molecular systems is important, as such studies enable researchers to design and imitate the potential behavior of low-dimensional structures that bear close structural resemblance to nanostructured materials found in nature.…”
Section: Introductionmentioning
confidence: 99%
“…The results were presented in the form of energy diagrams and bending moments plotted against the imposed axial rotations and had shown that the armchair-type SWCNT models exhibited predominantly higher twisting-bending stiffness and strength values relative to the zigzag-type SWCNTs. Litak [2017] simulated mechanical properties of SWCNT under the influence of axial loads, and estimated the critical SWCNT diameter using two different approaches under local shell buckling mode. For the same types of SWCNT models, Robinson and Adali [2017] applied a nonlocal continuum mechanics approach by implementing constitutive modeling of the tubes with research results obtained for both the uniformly distributed and triangularly distributed axial loads.…”
Section: Introductionmentioning
confidence: 99%